Proposed Model for Jakarta's Adaptation Strategy Towards a Global City from a Water Resilience Perspective - Arief Nasrudin; Margaretha Hanita; Abdul Rivai Ras (Jurnal Lemhannas RI, 2025)
Purpose: This study proposes a theoretical model to analyse water resilience as part of Jakarta's adaptation strategy towards becoming a resilient and sustainable global city, focusing on three aspects: water governance vulnerability, city resilience status, and adaptation strategy as the main policy response. Study Design/Methodology/Approach: This study uses a qualitative conceptual approach based on literature review and document analysis. The model was developed by integrating global city theory, social-ecological interaction theory, adaptation strategy, and national resilience. Relevant academic studies and policy documents on Jakarta’s water governance, PAM Jaya, piped water service expansion, and urban resilience were reviewed to identify the main dimensions and indicators of the proposed model. Findings: The proposed model connects three elements: water governance vulnerability as the independent variable, city resilience status as the mediator variable, and adaptation strategy as the dependent variable. The model suggests that higher water governance vulnerability may weaken city resilience, while stronger city resilience may support more effective adaptation strategies through infrastructure improvement, institutional strengthening, stakeholder collaboration, and community participation. Originality/Value: This theoretical model represents both the concept of water security and global city theory, which is embedded in its strategic framework with the Asta Gatra idea. It is also conceptually and policy relevant for other large cities in developing countries facing similar challenges in water governance, urban resilience, and urbanisation pressure.